Tingkat Kecemasan Mahasiswa pada Mata Kuliah Microteaching Berbasis Lesson Study - Krisdianto Hadiprasetyo; Annisa Prima Exacta; Dewi Susilowati (Universitas Veteran Bangun Nusantara, 2022)
The objective of this study is to determine the students’ anxiety level during a microteaching lesson based on the Lesson study and determine the faktors. This study is conducted in Mathematics education Universitas Veteran Bangun Nusantara Sukoharjo. The subjects are the students of 6 semesters. This is a qualitative method with the data on anxiety from the questionary of HARS. interview results. Subjects are drawn using purposive sampling. Data validation is done by triangulation of the data. Data analysis was performed at the stages of data reduction, data presentation, and conclusion. From the analysis 2 students with no anxiety, 3 students with light anxiety, and 3 students with moderate anxiety. Based on the results of data analysis on the degree of student anxiety during a microteaching lesson based on the Lesson study, i.e., the degree of anxiety is not anxiety, light, and moderate anxiety. Data from eight subjects that influence a student's level of anxiety: external faktors are influenced by friends and observers. Internal faktors that influence are lack of preparation for practice, lack of material preparation, lack of adaptability, and gender.